2017
DOI: 10.32918/nrs.2017.4(76).04
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for PSA Uncertainty Estimation and Application in Risk-Informed Decision-Making

Abstract: Uncertainties are very important in risk analysis and should be considered in the decision-making process. This paper proposes the methodology for estimation of PSA uncertainties in risk-informed decision-making. The methodology allows solving the complex task of identifying the sources of uncertainties, assessing their range, and providing an approach for consideration of PSA results with uncertainties in combination with other factors underlying risk-informed decision-making. The levels of uncertainties are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Jin et al 17 identified major contributors to completeness uncertainty and discussed the impact of completeness uncertainty on the reliability assessment of safety instrumented systems. Kukhotskyi et al 18 proposed to add a ''black box'' in the risk assessment model that represent model uncertainty. Bjerga et al 19 discussed the exact meaning of completeness uncertainty and proposed a practical approach for handling it in risk assessment.…”
Section: Completeness Uncertaintymentioning
confidence: 99%
“…Jin et al 17 identified major contributors to completeness uncertainty and discussed the impact of completeness uncertainty on the reliability assessment of safety instrumented systems. Kukhotskyi et al 18 proposed to add a ''black box'' in the risk assessment model that represent model uncertainty. Bjerga et al 19 discussed the exact meaning of completeness uncertainty and proposed a practical approach for handling it in risk assessment.…”
Section: Completeness Uncertaintymentioning
confidence: 99%